2012
DOI: 10.1155/2012/683097
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, DNA Damage, and c-Abl Signaling: At the Crossroad in Neurodegenerative Diseases?

Abstract: The c-Abl tyrosine kinase is implicated in diverse cellular activities including growth factor signaling, cell adhesion, oxidative stress, and DNA damage response. Studies in mouse models have shown that the kinases of the c-Abl family play a role in the development of the central nervous system. Recent reports show that aberrant c-Abl activation causes neuroinflammation and neuronal loss in the forebrain of transgenic adult mice. In line with these observations, an increased c-Abl activation is reported in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…Previous studies have demonstrated that c-Abl plays an essential role in PKCδ activation in response to oxidative stress (Gonfloni et al, 2012). In this context, c-Abl has been shown to phosphorylate PKCδ on tyrosine 311, which has been linked to apoptotic death in H 2 O 2 treated cells (Lu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that c-Abl plays an essential role in PKCδ activation in response to oxidative stress (Gonfloni et al, 2012). In this context, c-Abl has been shown to phosphorylate PKCδ on tyrosine 311, which has been linked to apoptotic death in H 2 O 2 treated cells (Lu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The ubiquitously expressed c-Abl is activated in response to diverse stimuli including growth factors, cell adhesion, oxidative stress and DNA damage (for a review see (Gonfloni et al, 2012)). Multiple lines of evidence document a role for c-Abl in oxidative stress-induced neuronal injury and high levels have been evidenced in postmortem PD brains (Ko et al, 2010; Brahmachari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our data support and extend previous studies that have reported a functional relationship between c-Abl and PKC␦ in response to genotoxic and oxidative stress (33)(34)(35). Both Yuan et al (34) and Sun et al (33) showed that hyperglycemia induced apoptosis of neural progenitor cells occurs through a PKC␦⅐c-Abl-dependent mechanism that involves tyrosine phosphorylation of PKC␦ and nuclear translocation of the PKC␦⅐c-Abl complex (36). Previous reports have demonstrated a role for members of the Src family of non-receptor tyrosine kinases in the regulation of PKC␦ (21,37,38).…”
Section: Discussionmentioning
confidence: 98%
“…While somatic mutations of PARK2 that decrease PARK2’s E3 ligase activity, compromising its ability to ubiquitinate cyclin E, are associated with cancer [121, 122], germline mutations of PARK2 were identified in patients with autosomal recessive juvenile Parkinsonism (ARJP) [123]. One of the main causes of PD is a redox imbalance in the brain [124]. Postmortem studies of PD patients reveal increased oxidation of lipids, proteins, and DNA, a severe decrease in glutathione concentration, and an accumulation of superoxide dismutase (SOD2) (reviewed in [125]).…”
Section: Cfs Gene Products With Roles In the Ddrmentioning
confidence: 99%